Eosinopenia Sebagai Penanda Dini Diagnosis Sepsis Bakterialis - Elisabet Sipayung; Endang Sembiring; Armon Rahimi (Fakultas Kedokteran USU, 2015)
Introduction :The early diagnosis of sepsis bacterialis plays an integral role in the morbidity and mortality of patients admitted to the hospitals and the intensive care unit (ICU) because it ensures the early administration of antibiotics. Thus the good markers of sepsis bacterialis which had good accuracy, easy to use and also cheap. Previously procalcitonin (PCT) was used to diagnose sepsis, unfortunetely it is expensive and this coupled with the fact that it takes a long time for the results to be attained and not always exist in developing countries, it is not an ideal marker for the early diagnosis of sepsis. In sepsis bacterialis, eosinophil absolut count decreased thus eosinopenia could be an early marker. The aim ofthis study was to know the accuracy of eosinopenia compared wih PCT to early diagnose of sepsis bacterialis. Methods : This cross-secional study was held from March 2014 until August 2014 in Internal medicine ward and ICU of H. Adam Malik Hospital Medan. Results : In this study the mean eosinophil count of the sepsis bacterialis patients was 27 sel/mm3• The cut-off of eosinopenia compared with PCT was 37 cells/mm3, then from statistical analysis the sensitivity of eosinophil was 94.9%, specificity was 92.3%, positive predictive value (PPV) was 92.5%, and negative predictive value (NPV) was 94.7%. Positive likelihood ratio was 12.3 and negative likelihood ratio was 0.06. From analysis of ROC curve area under the curve (AUC) was 92.4% (95% Cl:84.8% - 100%; p = 0.0001). Conclusion :Eosinopenia could be used to an early diagnosis of sepsis bacterialis. Keywords :sepsis bacteria/is, early diagnosis, proca/citonin, eosinopenia